Islamic bank’s fee income and risk: evidence from panel data analysis between Malaysia and Indonesia / Siti Sarah Mat Isa - Mat Isa, Siti Sarah (2017)
Fee income, a component of other operating income in Islamic banks, has become progressively important in raising the bank's earnings to counter declining net incomes due to competition from other financial competitors. However, it is vital for Islamic banks to determine any potential risk that will affect their performance due to this activity since they are channelling their focused toward fee income activities. By employing panel data analysis and quarter data of fourteen Malaysia Islamic banks and six Indonesia Islamic banks from the year 2009 to 2013, this study aims to examine the relationship between Islamic bank's fee income and characteristics with the risk in Malaysia and Indonesia. The empirical results proved that, fee income activities able to reduce Islamic bank's risk with weak significant impact. Besides that, Islamic banks with a larger value of total assets, total equity and total loans can offset the banks' risk. Therefore, for policy implication, the government should set up capital requirement specifically for fee income activities that suit with the Islamic bank's principle and risk to expand further on these activities. Islamic banks also are recommended to increase their assets value to ensure the sustainability of Islamic banking operation. In addition, to facilitate Islamic banking to remain sustainable and be competitive in the banking industry, it is imperative for Islamic banks to improve their risk management capabilities.